(untitled) (Czech Journal of International Relations, 2000)
On the basis of research in French archives, the author of the essay seeks to examine closely the personality and activities of the first French Consul in Prague, and also lo characterize the period and conditions under which this professional diplomat worked in Prague. The author also turns his attention to the Czech political scene and to the political situation in the Austrian monarchy, based on concrete examples (e.g. the commemoration of the 100th anniversary of the birth of Victor Hugo, the reaction of the press to the Dreyfus affair, disputes between the so-called “Young Czechs” and “Old Czechs”, the Badeni reforms or conflicts between the Czech and the German population). The French consulate in Prague was opened at the very end of the 19th century. Its objective was to promote bilateral Czech-French economic relations. However, the Austrian authorities lived with the assumption right from the start that here an endeavour was becoming evident to attribute to Prague a significance going beyond that of the capital of a province. That is why they tried to deny permission for its opening so that legally the German consulate was set up earlier. The author uses in his essay quotations from documents of that time to illustrate the way Valois’ views concentrated on the Czech nation. But he is said to have discovered later that the Czechs under no circumstances deserved the sympathy they enjoyed in France. After initial favourable judgements of the Czechs, the first French Consul made a 180 degree about-turn in the course of only a few years, which in some cases meant a shift, if not to hatred, at least to condescending high-handedness. This occurred at a time when a new place was explored in the context of the era when two nationalisms – the French and the Czech – combined in their common opposition to the German threat and when the Dreyfus affair, with international repercussions that cannot be ignored, had whipped up emotions not only in France hut throughout Europe to the great detriment of the 3rd republic whose foundations were still unstable and whose prestige was seriously jeopardized in the eyes of the world.